Kritik Sosial Instagram@Banggaber Dengan Wacana Kritis Teun Van Djik - Danang Aryono (DIGICOM : Jurnal Komunikasi dan Media, 2022)
Social criticism consists of two terms, namely from the word criticism and social. Criticism, in the Big Indonesian Dictionary, it is explained that criticism means criticism or feedback, sometimes accompanied by descriptions and considerations of the good and bad of a work, opinion and so on. While social has the meaning of making friends, together, associating, intending to understand events in society, namely human fellowship, to be able to try to bring about improvements in life together. Instagram is an application that is used to share photos and videos. Instagram itself is still part of Facebook which allows our Facebook friends to follow our Instagram account. Based on the research that researchers have done on social criticism content published by the @banggaber account. The analysis is based on a qualitative method with critical discourse analysis, using the research framework of the Teun A. van Dijk model. The text in the image uploaded to the Instagram account @banggaber contains social criticism, where is the creator processing social criticism becomes lighter to understand. In this study, the researcher wanted to see the message conveyed by the creator through his work. By examining the work of Instagram @banggaber using critical discourse analysis of the Teun model a Van Dijk, where there are three levels of analysis in the theory. The first level is the analysis structure, where the researcher observes the message conveyed in @banggaber's work. The second level is the analysis of the social cognition of the creator of @banggaber, Rizal Fahmi, focuses on the creator's cognition in determining the perspective of analysis in his work. The third level is how social criticism is compared to conditions that exist in society. From the three levels of analysis, data will appear that will be interpreted.